Logistics in dense cities - A study on large infrastructure projects - Jansson, Anna; Fredriksson, Anton (My University, 2017)
The densification of cities makes construction logistics in urban areas increasingly complicated. Construction sites are cramped, roads are congested, and restrictions in terms of delivery times and environmental zones create severe challenges regarding transport and logistics. Such problems regarding construction logistics are often overlooked, especially for infrastructure projects. The aim of the thesis is to examine how infrastructure projects can handle logistical challenges while constructing within increasingly dense cities. A qualitative study is suitable for in-depth scrutinising of the prerequisites and challenges with regard to construction logistics. This is done through a literature study and interviews with a selection of managers at Skanska. Two case studies are performed on infrastructure projects at Skanska, one at Hisingsbron, a project that has a traditional approach towards logistics, and one at Slussen, a project that uses innovative logistical solutions. The results show that project-based organisations tend to have few standardised solutions for logistics, and it is therefore a matter for each site manager to address logistics. Few resources are spent on improving construction logistics, a topic where competitive advantage can be gained. Additionally, the construction industry needs to stop blaming the uniqueness of each project, and instead focus on the similarities to create logistical solutions that can be used across many projects and involve many actors in the supply chain. The client - often a public actor - has a great opportunity and responsibility to influence contractors to adhere to logistical solutions, as there is potential to decrease rush hour traffic and the environmental impact when the number of trucks are reduced due to the more efficient transports. Finally, it is easier to convince site managers of the benefits of well-planned logistical solutions if the benefits are easy to visualise. It is therefore a suggestion to investigate the economical outcome of implementing various logistical solutions in the construction industry.
Keywords: Samhällsbyggnadsteknik; Civil Engineering